2010
DOI: 10.1002/elps.200900295
|View full text |Cite
|
Sign up to set email alerts
|

Stability constants determination of successive metal complexes by hyphenated CE‐ICPMS

Abstract: The study of radionuclides speciation requires accurate evaluation of stability constants, which can be achieved by CE-ICPMS. We have previously described a method for 1:1 metal complexes stability constants determination. In this paper, we present its extension to the case of successive complexations and its application to uranyl-oxalate and lanthanum-oxalate systems. Several significant steps are discussed: analytical conditions choice, mathematical treatment by non-linear regression, ligand concentration an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In the past few years, ACE has been widely used (i) to investigate chemical equilibria and measure stability constants of inorganic species and (ii) to determine the stable form of aqueous species [15,[17][18][19][20][21][22][23][24][25]. Models describing the formation of 1:1 complexes are often used [25][26][27] as well as models describing the formation of successive complexes using nonlinear regressions [15,17,19,21]. Moreover, commercial CE instruments perform measurements at a 5-60ЊC temperature range enabling to determine thermodynamic parameters such as entropy and enthalpy of reactions [25].…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, ACE has been widely used (i) to investigate chemical equilibria and measure stability constants of inorganic species and (ii) to determine the stable form of aqueous species [15,[17][18][19][20][21][22][23][24][25]. Models describing the formation of 1:1 complexes are often used [25][26][27] as well as models describing the formation of successive complexes using nonlinear regressions [15,17,19,21]. Moreover, commercial CE instruments perform measurements at a 5-60ЊC temperature range enabling to determine thermodynamic parameters such as entropy and enthalpy of reactions [25].…”
Section: Introductionmentioning
confidence: 99%
“…Petit et al 125 have extended their work, reported last year, on the determination of stability constants of 1 : 1 metal-ligand complexes to successive complexation reactions for the uranyland lanthanum-oxalate systems. They report evidence for a new La-oxalate complex: La(Ox) 3 3À .…”
Section: Capillary and Gel Electrophoresismentioning
confidence: 95%
“…Their CE–ICP–MS system consists of a CEi‐SP20 CE–Interface (Reeko Instrument Co., Xiamen, China) and an Agilent 7500ce ICP–MS (Agilent Technologies). Stability constants of radionuclide complexes were accurately evaluated for the speciation analyses .…”
Section: Development Of Instrumentationmentioning
confidence: 99%